Flash and Pattern Reversal Checkerboard Visual Evoked Potential Recording in Albinism Patients - Shushtarian, Seyed Mohammad Masoud (Journal of Ophthalmic and Optometric Sciences, 2020)
Purpose: Albinism includes a group of genetic disorders with decreased pigmentation. Patients with albinism experience photophobia due to the lack of pigments in the iris. Visual evoked potential (VEP) is one of the diagnostic techniques used in these patients. Flash and pattern-reversal checkerboard VEPs are two stimulation techniques to record VEP. The present work aimed to compare these two techniques in albinism patients and look for the optimum one. Materials and Method: Flash and pattern-reversal checkerboard VEPs were recorded in 20 albinism patients. The latency (msec) and amplitude (µv) of VEP, P100 peak were measured for each patient, and the results were evaluated and compared. Results: The patients aged between 10-20 years. The population included an approximately equal number of both sexes, and the best corrected visual acuity ranged from 1/10 to 3/10. The difference was statistically significant between the two types of stimulation regarding the latency of VEP, P100 peak. However, the peak difference was not significant between the two types of stimulation as far as amplitude was concerned. Conclusion: The pattern-reversal checkerboard is a suitable technique to record VEP in albinism patients, although using flash VEP is inevitable in some cases.